2017
DOI: 10.1080/09593330.2017.1417492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cationic polyacrilamide flocculant on high-solids’ anaerobic digestion of sewage sludge under thermophilic conditions

Abstract: Treatment of sewage sludge (SS) by biodegradable polyacrylamide-based flocculants (PAM) is considered to be an effective way to increase total solids' (TS) content prior to anaerobic digestion (AD). However, data on how PAM addition influences the efficiency of AD process are quite contradictory; moreover, no data are available for thermophilic AD (TAD). This study showed that at an optimal inoculum-to-substrate ratio (ISR, 55/45), PAM addition resulted in some decrease in initial methane production during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…They also revealed that PAM can be hydrolysed at different position of its carbon-chain backbone, and that the hydrolysed PAM fragments combined with tyrosine-rich proteins to form colloid complexes during the HS-AD of SS. These findings were further confirmed by Litti et al (2019), who reported that the addition of PAM led to decreased methane production in the HS-AD of SS. The researchers attributed this to the formation of large flocs and the consequent suppression of mass transfer.…”
Section: The Main Intrinsic Factors Affecting the Hs-ad Of Sssupporting
confidence: 64%
See 2 more Smart Citations
“…They also revealed that PAM can be hydrolysed at different position of its carbon-chain backbone, and that the hydrolysed PAM fragments combined with tyrosine-rich proteins to form colloid complexes during the HS-AD of SS. These findings were further confirmed by Litti et al (2019), who reported that the addition of PAM led to decreased methane production in the HS-AD of SS. The researchers attributed this to the formation of large flocs and the consequent suppression of mass transfer.…”
Section: The Main Intrinsic Factors Affecting the Hs-ad Of Sssupporting
confidence: 64%
“…Methanogenic activity decreases at a pH < 6.3 or>7.8 -Lay et al, 1997;Bitton, 2002;Gerardi, 2003;Xu et al, 2020a Ammonia -Boráň et al, 2010;Luo et al, 2011;Qi et al, 2011;Dai et al, 2014b;Dai et al, 2015;Litti et al, 2019;Zhi and Zhang, 2019 Rheological properties The stability decreases with an increase in the viscosity or an decrease in the diffusion coefficient -Decrease with high viscosity or low diffusion coefficient - Kirby, 1988;Slatter, 1997;Cheng and Li, 2015;Sajjadi et al, 2016;Zhang et al, 2016;Hu et al, 2018 Notes: HS-AD: high solid-anaerobic digestion; SS: sewage sludge; VS: volatile solid; TS: total solid; SRT: solid retention time; FAN: free ammonia-nitrogen; TAN: total ammonia-nitrogen; VFAs: volatile fatty acids; PAM: polyacrylamide. Nges and Liu (2010) shortened the SRT from 35 days to 12 days in the HS-AD of SS under both thermophilic and mesophilic conditions, and found that this increased the biogas-production rate and volumetric methane productivity, and decreased the VS-reduction efficiency.…”
Section: Factors Affecting the Hs-ad Of Ssmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperatures of the injector, oven and thermal conductivity detector were set to 45 • C, 60 • C and 200 • C, respectively. The gases were calibrated using an external standard method based on a standard curve of detector response to known gas concentrations [41].…”
Section: Methodsmentioning
confidence: 99%
“…The addition of polyacrylamide‐based flocculants (40 mg/g total solids) was shown to be effective in restoring methanogenesis in thermophilic anaerobic digestion even with the inhibition of accumulation of volatile fatty acids and pH decrease (Litti et al, 2019). The addition of zerovalent iron nanoparticles to anaerobic digesters resulted in an increase biogas yield 132 (control) to 310 ml/gVS with an increase in the percentage of methane from 63.2% (control) to 77.6%, which corresponded to a maximum yield of 238 mLCH 4 /gVS (Lizama, Figueiras, Pedreguera, Figueiras, Pedreguera, & Ruiz Espinoza, 2019).…”
Section: Sludge To Biosolids: Treatment Advancesmentioning
confidence: 99%